PENGARUH LOAN TO DEPOSIT RATIO, CAPITAL ADEQUACY RATIO, DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arief Rachmawan Assegaf (Jurnal Ekonomi dan Industri, 2023)
The purpose of this research is to analyze the influence of loan to deposit ratio, capital adequacy ratio, and return on equity ratio on stock prices of banking companies listed on the Indonesia Stock Exchange. This research was designed with a quantitative method. The sample was selected by purposive sampling method with the criteria of 15 banking companies with the largest market capitalization value, totaling 15 samples with a research period of 5 years. Analysis methods used this research were simultaneously and partially regression analysis. The results of this research indicate that partially loan to deposit ratio has a negative and significant influence on stock prices, capital adequacy Ratio has no significant influence on stock prices, and return on equity ratio has a positive and significant influence on stock. Meanwhile, simultaneously loan to deposit ratio, capital adequacy ratio, and return on equity ratio have a significant influence on stock prices.